Long-term impact of maternal pre-pregnancy BMI on the risk of overweight/obesity in preschool children: mediation by infant birth weight and BMI trajectory group from 0 to 2 years - Ang Mao; Shu-Qin Yang; Ying-Juan Luo; Yan Ren; Xu Yan; Yu-Rong Qiu; Xiao Yang (BMC Public Health)
Abstract Background Obesity is a complex multisystem disease that affects almost every organ system. Studying the early determinants of obesity and implementing targeted interventions have positive implications for promoting long-term health. Therefore, this study was to evaluate the impact of maternal pre-pregnancy overweight or obesity, weight gain rate (WGR) during the second and third trimesters, infant birth weight (IBW) and BMI trajectory group (BMI-TG) from 0 to 2 years on overweight or obesity in preschool children. Methods A retrospective cohort analysis of data obtained from a hospital was performed using chain-mediated effects to analyze the direct and indirect effects of prepregnancy body mass index (ppBMI)on preschool children’s body mass index (pcBMI), and mediated by three variables: WGR, IBW and BMI-TG. Results We found that the effect of ppBMI and pcBMI was significantly mediated by IBW and BMI-TG. After adjusting for confounding factors, the total effect of ppBMI on pcBMI was estimated to be 0.1965 (bootstrap 95% CI: 0.1154–0.2783), the direct effect was 0.1562 (bootstrap 95% CI: 0.0750–0.2362), and the indirect effect was 0.0403 (bootstrap 95% CI: 0.0219 ~ 0.0651). The mediating effect accounted for 20.5% of the variance, indicating that 20.5% of the impact of ppBMI on pcBMI was mediated by two mediating factors: IBW and the BMI-TG. Conclusions Maternal overweight/obesity before pregnancy had a significant impact on overweight/obesity in preschool children and was mediated by two main factors: IBW and the BMI-TG.